Bridging the Ocean: Some Aspects of the Iranian Cultural Presence in Southeast Asia with Emphasis on the Siamese Kingdom of Ayutthata - Marcinkowski, Muhammad Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Bridging the Ocean: Some Aspects of the Iranian Cultural Presence in Southeast Asia with Emphasis on the Siamese Kingdom of Ayutthata